2008
DOI: 10.1007/s11113-008-9105-6
|View full text |Cite
|
Sign up to set email alerts
|

A Panel Based Analysis of the Effects of Race/Ethnicity and Other Individual Level Characteristics at Leaving on Returning

Abstract: Return migration, Tempo of migration, Race/ethnic, Internal migration, Repeat migration,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…In addition, infants' propensity to move (with their parents) is high. Note also that, when there really is a choice, studies based on primary collected data or survey data employ region of residence at other ages than at birth, typically during adolescence/young adulthood (eg, DaVanzo and Morrisson, 1981;Dienel et al, 2006;Stockdale, 2006;Wilson et al, 2009). On the other hand, studies of geographical attachment instead stress the length of time spent somewhere as a key factor, although other predicators have also been attributed importance (Lewicka, 2011).…”
Section: Previous Studies and How The Key Concepts Have Been Operatiomentioning
confidence: 99%
“…In addition, infants' propensity to move (with their parents) is high. Note also that, when there really is a choice, studies based on primary collected data or survey data employ region of residence at other ages than at birth, typically during adolescence/young adulthood (eg, DaVanzo and Morrisson, 1981;Dienel et al, 2006;Stockdale, 2006;Wilson et al, 2009). On the other hand, studies of geographical attachment instead stress the length of time spent somewhere as a key factor, although other predicators have also been attributed importance (Lewicka, 2011).…”
Section: Previous Studies and How The Key Concepts Have Been Operatiomentioning
confidence: 99%
“…The initial move is, however, less likely to satisfy movers’ needs because they may have had little information about new environments and be disappointed by the discrepancy between their expected and actual gains (McHugh, Hogan, and Happel 1995). As a result, some of the initial movers seek additional destinations while others return to their original places (McHugh et al 1995; Wilson et al 2009). The sequential migration patterns vary by location-specific capital and length residing in the place (DaVanzo and Morrison 1981) and also by personal traits which are not captured with explanatory variables typically available in major data-sets (DaVanzo 1983; Gabriel and Schmitz 1995).…”
Section: Background and Research Questionsmentioning
confidence: 99%
“…non‐Hispanic whites, non‐Hispanic blacks, and Hispanics). Currently, there is limited research on the net differences between racial and ethnic groups on the propensity for repeat migration (although see Wilson et al ., ), and research has yet to rigorously examine the racial and ethnic differences in the effects of community characteristics on repeat migration. A focal objective of this study then is to further develop and test the tenets of the cultural constraints hypothesis – a hypothesis that anticipates divergent community effects on migration propensities for minority and majority group members – specifically as it relates to patterns of repeat migration.…”
Section: Introductionmentioning
confidence: 99%
“…Long (), among others, found that those with higher levels of education are more likely to engage in internal migration than those with lower levels of education. However, there is one notable exception to this general pattern: lower levels of education are associated with higher rates of return migration (DaVanzo and Morrison, ; DaVanzo, ; Wilson et al ., )…”
Section: Introductionmentioning
confidence: 99%